Islamic legal maxims analysis on orthognathic surgery and treatment - Nor Azura Ahmad Tarmidzi,; Wan Abdul Fattah Wan Ismail,; Nalisha Mohamed Ramli,; Nadia Halib,; Nur Akilah Abdul Ghaffar, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Medical treatment by Muslim doctors will sometimes be influenced by Islamic law and ethics rather than solely medical consideration. Muslim patient’s sometimes need reassurance that modern medicine that offered to them is also acceptable by Islamic law. Orthognathic deformities are condition which associated with discrepancies of the jaw. These deformities resulted from different rates of growth of the maxilla, the mandible or both. Performing cosmetic surgery seems to change the creation of Allah and the original law of changing Allah’s creation is prohibited. In assessing the orthognathic surgery law for patients with this dentofacial defect, the researcher found that the main issues that need to be investigated are the difficulties existed (Masyaqqah) and the level of patient harm in addition to the intention or purpose of performing orthognathic surgery. However, according to the principles of the Islamic jurisprudence, orthognathic surgery is permitted based on the principles such as ad-darar yuzal, al-musyaqqah tajlibu al-taisir, al-darurat tuqaddiru biqadaruha, irtikab akhaf al-dhararain, al-darurat tubihu mahzurat and al-umur bimaqasidiha. Orthognathic surgery can be done because the purpose is to treat defects and restore function. This objective is very consistent with the fiqh rules that stated, every harm and distress should be eliminated.